ANALISIS FUNGSI MAJELIS PERMUSYAWARATAN RAKYAT (MPR) DALAM HIERARKI PERUNDANG-UNDANGAN - Kevin Andreas Halomoan Tambunan; Ridha Nababan; Rimma Anisa Siagian; Roslin Naiborhu; Putri Paulina Sembiring (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The role of the People's Consultative Assembly (MPR) in the Indonesian constitutional system as well as the hierarchy of laws and regulations in Indonesia is discussed in this report. The legal sequence system known as the "hierarchy of statutory regulations" aims to provide legal certainty by ensuring that lower regulations do not conflict with higher regulations. The 1945 Constitution functions as the highest source of law. The MPR has a strategic role in the Indonesian government structure, they can change or enact the 1945 Constitution, elect the President and Vice President, and assess government performance. The Outlines of State Policy (GBHN) were established by the MPR before the amendments to the 1945 Constitution, after the reform, other regulations were added. In addition, this report explains how the MPR is involved in making national strategic policies and monitoring laws. To study the role of the MPR in the hierarchy of statutory regulations and its influence on strengthening the Indonesian legal system, this research uses a literature study with descriptive analysis. It is hoped that the results of this research will increase understanding of the role of the MPR in maintaining the consistency and continuity of the Indonesian legal and regulatory system.